CP-25, a Novel Anti-inflammatory and Immunomodulatory Drug, Inhibits the Functions of Activated Human B Cells through Regulating BAFF and TNF-alpha Signaling and Comparative Efficacy with Biological Agents - Zhang, Feng; Shu, Jin-Ling; Li, Ying; Wu, Yu-Jing; Zhang, Xian-Zheng; Han, Le; Tang, Xiao-Yu; Wang, Chen; Wang, Qing-Tong; Chen, Jing-Yu; Chang, Yan; Wu, Hua-Xun; et al. (Frontiers in Pharmacology, 2017)
Paeoniflorin-6′-O-benzene sulfonate (code: CP-25) is the chemistry structural modifications of Paeoniflorin (Pae). CP-25 inhibited B cells proliferation stimulated by B cell activating factor belonging to the TNF family (BAFF) or Tumor necrosis factor alpha (TNF-alpha). CP-25, Rituximab and Etanercept reduced the percentage and numbers of CD19+ B cells, CD19+CD20+ B cells, CD19+CD27+ B cells and CD19+CD20+CD27+ B cells induced by BAFF or TNF-alpha. There was significant difference between CP-25 and Rituximab or CP-25 and Etanercept. CP-25 down-regulated the high expression of BAFFR, BCMA and TACI that was stimulated by BAFF or TNF-alpha. The effects of Rituximab and Etanercept on BAFFR or BCMA were stronger than that of CP-25. CP-25, Rituximab and Etanercept down-regulated significantly the expression of TNFR1 and TNFR2 on B cell stimulated by BAFF or TNF-alpha. CP-25, Rituximab and Etanercept down-regulated the expression of MKK3, P-p38, P-p65, TRAF2 and p52 in B cells stimulated by BAFF and the expression of TRAF2 and P-p65 in B cells stimulated by TNF-alpha. These results suggest that CP-25 regulated moderately activated B cells function by regulating the classical and alternative NF-κB signaling pathway mediated by BAFF and TNF-alpha-TRAF2-NF-κB signaling pathway. This study suggests that CP-25 may be a promising anti-inflammatory, immune and soft regulation drug.